Pengembangan Media Pembelajaran Papan Dan Kartu Misteri (PAKARMIS) Berbasis Quiz Team Pada Mata Pelajaran Korespondensi di SMK Adhikawacana Surabaya - Fitriani Damayanti; Durinda Puspasari (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
The purpose of this study was to determine the results of the development of quiz team-based board and mystery learning media (PAKARMIS) on correspondence subjects at Vocational School Adhikawacana Surabaya, the feasibility of board and card learning media mystery (PAKARMIS) based on quiz teams on correspondence subjects at SMK Adhikawacana Surabaya, and students' responses to the quiz team-based board and mystery learning media (PAKARMIS) on correspondence subjects at SMK Adhikawacana Surabaya. This type of research is research and development (R&D) using the ADDIE model. The trial subjects were 20th grade OTKP 3 students of Vocational School Adhikawacana Surabaya, totaling 20 people chosen randomly. Data collection instruments used in this study were expert validation sheets and student questionnaire responses. The results showed that the media developed were included in the feasible category by obtaining a percentage of ratings from material experts at 89% and media experts at 88%, all of which were included in very strong interpretations. While the results of student responses to the learning media developed obtained a percentage of 87% with a very strong interpretation. The results of the trial show that students are more interested in conducting learning activities using quiz team-based board and mystery learning cards (PAKARMIS) compared to using only blackboards and markers. Students are more active and enthusiastic in learning to use these learning media. So it can be concluded the results of this development research are said to be very feasible to be used as learning media.